Constructivism in practical philosophy - Lenman, James; Shemmer, Yonatan (Oxford : Oxford University Press, 2012)
This volume presents 12 original papers on the idea that moral objectivity is to be understood in terms of a suitably constructed social point of view that all can accept. The contributors offer new perspectives, some sympathetic and some critical, on constructivist understandings of morality and reason.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Constructivism (Philosophy)